Keladi-Sagu, Si-Ipar: Implementasi Kebijakan Binmas Noken di Kota Jayapura - Kendek, Piter; Silo, Akbar (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2024)
This article discusses the implementation of the BINMAS Noken policy in Jayapura City, focusing on the factors that support or hinder its effectiveness. The research method used is descriptive qualitative, with data collected through interviews and observations. The analysis process includes data reduction, presentation, and conclusion drawing. The study found that the implementation of BINMAS Noken in Jayapura City consists of two programs: Si-Ipar, which focuses on “Polisi pi Ajar”(Police teaching the kids), and Keladi-Sagu, which “Kesehatan Lambang Diri Sehat Guna” (promotes self-use of health symbols). The communication aspect involves structured distribution with inter-agency coordination, utilizing social media as a communication medium both internally and with the community. The program also involves the Binmas apparatus and supporting resources. The task force receives incentives to enhance performance and demonstrates consistency and commitment to the program. The bureaucratic structure follows standard operating procedures. Internal supporting factors include high motivation and enthusiasm for work, as well as incentives for task force personnel. Externally, the local government is supportive, collaborating in program preparation and implementation. However, there are internal inhibiting factors such as personnel with double duties and inadequate logistical support, resulting in delays. Externally, community participation is limited due to a lack of motivation and involvement.